Leadership Roles in Innovation Management and School-Based Budgeting to Improve School Effectiveness - Lahersa, Elpi; Anggun, Anggun; Sinurat, Oktavia; Surnika, Vista Meranda; R. Duran, Sharicce Jyla (Indonesian Educational Administration and Leadership Journal (IDEAL), 2025)
This think about points to look at and analyze the part of authority in school-based development administration and budgeting to make strides school viability. Employing a quantitative approach and overview methods, information was collected through surveys disseminated to school principals, directors, and instructors over different schools in a chosen locale. The ponder included 400 respondents, decided through a stratified arbitrary testing strategy. Information investigation was conducted utilizing the PLS-SEM strategy to recognize the coordinate and circuitous impacts of administration on advancement administration, budget allotment, and by and large school viability. The comes about of the consider demonstrate that (1) authority emphatically impacts the viability of development administration, (2) school-based budgeting contributes to improved school execution, (3) the principal’s authority plays a basic part in supporting inventive hones, (4) administration impacts budget assignment methodologies, and (5) compelling budgeting and advancement administration together contribute to moving forward by and large school viability. In this way, the discoveries recommend that solid authority, successful administration of development, and key budget arranging are fundamental for improving school execution. Keywords: word; leadership, innovation management, school based budgeting, school effectiveness.